Polyethylene glycol-superoxide dismutase inhibits lipid peroxidation in hepatic ischemia/reperfusion injury - Nguyen, Wyn D (BioMed Central, 1999)
BACKGROUND: Hepatic injury after ischemia/reperfusion is attributed to the development of oxygen free radical (OFR)-mediated lipid peroxidation - a process that can be measured through its byproducts, specifically malondialdehyde. The use of free radical scavengers can offer significant protection against OFR-induced liver injury. We hypothesize that a new potent OFR scavenger, polyethylene glycol-superoxide dismutase (PEG-SOD), can inhibit OFR-mediated lipid peroxidation in hepatic ischemia/reperfusion injury. METHODS: Twelve male Sprague-Dawley rats (300-350 g) were subjected to occlusion of the left and middle hepatic arteries and portal veins for 90 min, followed by 120 min reperfusion. PEG-SOD (5000 units/kg) was given intravenously before vascular occlusion and again immediately upon reperfusion to six rats. Normal saline was given to the remaining six rats to be used as a control group. The right hepatic lobe (used as internal control) and left hepatic lobe were harvested separately and tissue malondialdehyde was measured. RESULTS: A marked increase in lipid peroxide was found in the normal saline group after 2 h reperfusion. Treatment with PEG-SOD prevented the rise in tissue malondialdehyde. The mean difference in the malondialdehyde between the left and right hepatic lobes were 13.20 ± 6.35 and 1.70 ± 3.65 nmol/g in the normal saline (control) and PEG-SOD groups, respectively. This difference was found to be statistically significant (P < 0.005) using Student's t-test. CONCLUSIONS: PEG-SOD can effectively attenuate hepatic ischemia/reperfusion injury by inhibiting OFR-mediated lipid peroxidation.